2009
DOI: 10.1063/1.3264839
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics and mechanical limitation of polycrystalline silicon thin film transistor on steel foil under strain

Abstract: This work investigates the effect of mechanical strain on the electrical characteristics of polycrystalline silicon thin film transistors ͑poly-Si TFTs͒. Poly-Si TFTs were fabricated on steel foil substrate and characterized under the strain ranging from Ϫ1.2% to 1.1% induced by bending. The electron mobility increased under tensile and decreased under compressive strain while that of the hole exhibited an opposite trend. For both n-channel and p-channel poly-Si TFTs, the threshold voltage decreased and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…They have superior thermal and electrical conductivities. Moreover, they can offer superior chemical resistance in many environments compared to plastic [2], [3]. In order to improve the thermal dissipation, metallic bonding can be used.…”
Section: Introductionmentioning
confidence: 99%
“…They have superior thermal and electrical conductivities. Moreover, they can offer superior chemical resistance in many environments compared to plastic [2], [3]. In order to improve the thermal dissipation, metallic bonding can be used.…”
Section: Introductionmentioning
confidence: 99%
“…More significant degradation occurs when the TFT is bent biaxially and becomes greater with increasing bending. Many studies [8][9][10][11][12] have analysed the failure of TFTs under mechanical stress and found that the threshold voltage drops and the stress increases the trapping of the TFT, affecting the degradation of its electrical properties. In addition, carrier transport is also affected by changes in the effective mass of the carriers, which is caused by strain.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible displays have attracted considerable attention as next-generation displays that are flexible, light, and not easily breakable [ 1 ]. As the active layer in flexible displays, many materials have been used, such as amorphous silicon [ 2 , 3 ], low-temperature polycrystalline silicon [ 4 , 5 ], semiconductor oxides [ 6 , 7 ], and organic materials [ 8 , 9 ]. Amorphous indium-gallium-zinc-oxide (a-IGZO) films offer the advantages of high mobility, small sub-threshold swing, low leakage current, and good uniformity owing to their amorphous phase, which makes them suitable for manufacturing large-area displays [ 10 ].…”
Section: Introductionmentioning
confidence: 99%